The Risks of Narkolema (Visual-Based Narcotic Effects) on Children - Munisa Munisa; Rita Nofianti; Rika Widya (Jurnal Pendidikan Anak Usia Dini, 2026)
Narkolema (narcotics through visual exposure) refers to the exposure of children to visual content that is inappropriate for their developmental stage, such as violence, pornography, and excessive use of digital media. Children are in a highly plastic stage of brain development; therefore, visual stimuli received through the sense of sight play a crucial role in shaping cognitive functions, emotional development, and behavior. Addictive and overstimulating visual exposure can affect attention systems, emotional regulation, and self-control in children. This study aims to examine the dangers of narkolema on child development from the perspectives of neuroscience and developmental psychology. The method employed was a literature review using a qualitative descriptive approach based on relevant scientific sources. The findings indicate that uncontrolled visual exposure can disrupt the balance between the limbic system and the prefrontal cortex, resulting in increased impulsive behavior, difficulties in concentration, and emotional instability. Therefore, active involvement of parents and educators is essential through guidance and the strengthening of digital literacy to protect children from the negative impacts of narkolema.